Penerapan Panduan Operasional dalam Merawat Atribut WTBOS - Sea Games, Rahmat Gino (Puitika, 2024)
This paper examines the properties and objects of WTBOS, which was designated as a UNESCO World Heritage Site in 2019. The method involves comparing the conditions of the properties and objects at the time of or after their nomination with their current state in 2024. Observations reveal that some WTBOS properties and objects remain well-preserved, serving purposes such as tourism, education, and functional use. However, some properties and objects are in disrepair, have not been maintained, or have even disappeared. Maintaining WTBOS properties and objects is essential to preserve their condition, including long-term utilization. The findings of this paper highlight the need for strategies and significant steps in WTBOS management, ensuring their inclusion in sustainable management and utilization practices.